Micronucleus and different nuclear abnormalities in wild birds in the Cerrado, Brazil - Silveira, Elaine Divina Rodrigues; Benvindo-Souza, Marcelino; Assis, Rhayane Alves [UNESP]; dos Santos, Cirley Gomes Araújo; de Lima Amorim, Nathan Pereira; Borges, Rinneu Elias; de Melo, Celine; de Souza Santos, Lia Raquel (Springer Nature, 2022)
Free-living birds play an important role as bioindicators in natural environments. In this study, we used the micronucleus test and nuclear erythrocyte abnormalities to investigate the difference in the genotoxic damage frequency between animals in agricultural areas (soybean planting) in relation to the conserved area. It was also discussed the bird’s eating habits, which are important for ecotoxicological analysis. The results point to a difference between the insectivorous, granivorous, and omnivorous guilds. The omnivore Gnorimopsar chopi was the species that most exhibited micronucleus frequency in the protected area. In the agricultural area, the animals did not differ in the genotoxic damage frequency. In the comparison between common species in both environments, G. chopi from the agricultural area showed a micronuclei frequency almost three times higher in relation to specimens collected in the conserved area. Based on these results, this study adds to the efforts of using the micronucleus test as a simple and accessible tool for biomonitoring the wild fauna. It can be concluded that the passerine, G. chopi, due to its higher genotoxic damage frequency may be a strong candidate to indicate environmental health.
Keywords: Agricultural environment; Avifauna; Ecotoxicology; Genotoxicity; Micronuclei; Trophic guild